(untitled) - Russell, Keri; 1976-; Pegg, Simon; 1970-; 1961-; Fishburne, Laurence; Monaghan, Michelle; Marsan, Eddie; Rhys-Meyers, Jonathan; 1967-2014; 1968-; Crudup, Billy; et al. (Hollywood, California, 2011)
Ethan Hunt has retired from active duty as a super-spy in order to train new IMF agents. He is called back into action to confront the toughest villain he has ever faced - Owen Davian, an international weapons and information provider with no remorse and no conscience. Hunt assembles his team - his old friend Luther Strickell, transportation expert Declan, and background operative Zhen, in order to rescue Lindsey, one of his trainees, who was kidnapped while on a surveillance detail of Davian. It soon becomes evident that Davian is well-protected, well-connected, and downright malicious, forcing Hunt to extend his journey back into the field in order to rescue his wife, Julia, and uncover an IMF double agent in the process.
Keywords: Spies; Drama; Drama; Kidnapping; Drama; Illegal arms transfers